Peran Spiritual dan Etika Perempuan dalam Karya Al-Ghazali: Implikasi untuk Pendidikan Gender - Putri Humaira Djufri; Mustamin Giling (Al-Kindi, 2026)
This research explores the relationship between women's ethics in Al-Ghazali's thought and gender education in the contemporary Muslim world. Al-Ghazali, a prominent 11th-century Islamic scholar, emphasized the importance of spirituality and morality in daily life, including in the context of women. Through qualitative research using literature review methods, this study analyzes Al-Ghazali's works, particularly